شعرية الفضاء الطباعي وتمثلاته البصرية في رواية " سيرك عمار" لسعيد علوش - مكناسي, آمال; سريدي, فتيحة (جامعة الوادي - University of Eloued, 2021)
يعد التشكيل البصري مظهرا من مظاهر التجريب في الرواية المعاصرة، التي اتجه أصحابها إلى استحداث طرائق تشكيلية مختلفة ترافق عملية الكتابة الروائية، وإعادة هندسة فضائها الطباعي. لذلك سعت هذه الدراسة إلى الوقوف على أبرز عناصر الفضاء الطباعي في رواية "سيرك عمار" للروائي "سعيد علوش"، بدءا من استقراء فضاء الكتابة والتصفيح، مرورا إلى نوع الخط وسمكه وطريقة تشكيله، إلى جانب توظيف الرسم والصور الفوتوغرافية المصاحبة للنص الروائي، محاولين استنطاق القيم الجمالية البصرية لهذا الفضاء، وقدرته الإنتاجية في توليد الدلالات. Abstract: Visual composition is a manifestation of experimentation in contemporary novels, whose authors tend to develop different formative methods that accompany the process of narrative writing and the re-engineering of its printing space. This study therefore seeks to identify the most prominent elements of the printing space in Said Allouche's novel "Ammar's Circus"; it extrapolates the space of writing and pagination, through the type of calligraphy and its thickness and the way it is formed, as well as examining the use of drawing and photographs accompanying the narrative text, trying to question the visual aesthetic values of this space, and its productive ability to generate semantics. key words: Poetry; Print Space; Visual Composition; Contemporary Novel; Ammar's Circus.
مقال
Keywords: الشعرية؛ الفضاء الطباعي؛ التشكيل البصري؛ الرواية المعاصرة؛ سيرك عمار.